The Relationship between the Antitumor Effect of the IL-12 Gene Therapy and the Expression of Th1 Cytokines in an HPV16-Positive Murine Tumor Model. (7th April 2014) - García Paz, Flor; Madrid Marina, Vicente; Morales Ortega, Ausencio; Santander González, Abimelec; Peralta Zaragoza, Oscar; Burguete García, Ana; Torres Poveda, Kirvis; Moreno, José; Alcocer González, Juan; Hernandez Marquez, Eva; Bermúdez Morales, Victor
Abstract : Objective . The goal of the present study was to investigate the effect of IL-12 expressed in plasmid on the Th1 cytokine profile in an experimental HPV16-positive murine tumor model and the association with the IL-12's antitumor effect. Methods . Mice were injected with BMK-16/myc cells to establish HPV16-positive tumor and then pNGVL3-mIL-12 plasmid; pcDNA3 plasmid or PBS was injected directly into tumor site. The antitumor effect of the treatment was evaluated and the cytokines expression profile in each tumor tissue was analyzed. Results . Treatment with pNGVL3-mIL-12 plasmid had a significant antitumor effect, and a Th2-Th3-type cytokines prolife was detected in the murine tumor model with expression of the cytokines IL-10, IL-4, and TGF- β 1. However, after the tumor was treated with three intratumoral injections of plasmid containing IL-12 cDNA, it showed a cytokine profile associated with Th1 with expression of IL-2, IL-12, and IFN- γ cytokines and reduced expression of IL-10, IL-4, and TGF- β 1. Conclusions . The treatment with the IL-12 gene in the experimental HPV16-positive tumor model promoted the activation of the cellular immune response via expression of a Th1-type cytokine profile and was associated with the inhibition of tumor growth. Thus, IL-12 treatment represents a novel approach for gene therapy against cervical cancer.